Evaluation of Household Radiation Exposure and Safety after Ambulatory Radioiodine Ablation Therapy - Martin, Ralph; Silva, Frieda; M Colon, Annel; Román, Diego; González T, Brenda (Journal of Thyroid Cancer, 2016)
Objective: Radiation exposure to the general public and patients undergoing diagnostic or therapeutic procedures is of great concern, especially to the medical community. Revision of Nuclear Regulatory Commission rules several years ago yield new recommendations for the administration of therapeutic doses of 131-Iodine that included the release criteria. The guidelines for ambulatory treatment included patient education and radiation safety measures to minimize exposure and contamination. Our goal in this study was to evaluate patient compliance with the radiation safety instruction protocols given to them before the therapeutic dose and monitor radiation levels in different house areas at different times after an ablation therapy of 3700MBq or more. Method: Patients with well differentiated thyroid cancer being evaluated for ablation therapy with 131-Iodine were invited to participate. A thorough set of instructions on radiation protection were given verbally and in writing. Patient house was assessed with a Geiger Muller detector at 24 and 72 hours or above to obtain direct radiation levels in several areas. Patient radiation levels were also monitored. Results: A total of 12 patients have been included, 11 females and 1 male, median age was 53 years. Tumor histology was 10 papillary, 2 papillary-follicular variant and 1 follicular carcinoma; 92% of the cases were T1, N0, M0. Home location was urban in 77% and rural in 33% of the patients; 67% of the patients had an educational level between 9-12 grade. Radioiodine doses range from 3441-5994MBq. None of the patients had a relatives or companion in the house. Mean patient exposure 24 hours after the dose at 1 meter was 12mrem/hr, 0.120mSv/h; this represented a retained dose of 2181MBq (59mCi). Only one patient (T1, Nx, M1) had an exposure rate at 1 meter of 100mrem/hr (1mSv/hr) at 24 hours. At 72 hours the exposure changed to 4mrem/hr, 0.040mSv/hr, retained dose of 725.2MBq (19.6mCi). Higher exposure rates in the house were at 24 hours in the bed and pillows (7mrem/hr), kitchen trash (13mrem/hr) and bathroom sink (8mrem/hr). The exposure rates at the toilet and shower were similar (3-4mrem/hr). There was a significant decreased in the exposure rate at 72 hours in all house areas. Patients with the higher exposure rates were those with metastatic disease, and small living facilities. Patients living in rural or urban location had no difference in the exposure rate. The educational levels were not related either to the exposure rate. Conclusion: Patient compliance with radiation protection instructions and Nuclear Regulatory Commission release criteria was good. Radiation exposure levels in the house areas are safe. Special instructions must be design to minimize contamination in the bathroom and kitchen Caution is recommended in the release of patients with extensive metastatic disease and doses of 5920MBq or more.
Keywords: Radiation Safety; Radioiodine Therapy; Thyroid Cancer; Ablation Therapy; Radiation Exposure; Iodine-131